Linear Lupus Erythematosus Profundus as an Initial Manifestation of Systemic Lupus Erythematosus in a Child. Issue 3 (18th December 2012) - Fernandes, Sónia; Santos, Sónia; Freitas, Isabel; Salgado, Manuel; Afonso, Ana; Cardoso, Jorge
Abstract The case of a 13‐year‐old Caucasian girl with a 1‐year history of a linear plaque on her thigh is reported. Histopathologic examination of the incisional biopsy tissue established the diagnosis of lupus erythematosus panniculitis. Six months later she developed the clinical and laboratory criteria for the diagnosis of systemic lupus erythematosus (SLE). She was treated with azathioprine and oral prednisolone, with a favorable clinical outcome. Our case illustrates a child with linear lupus erythematosus profundus as an initial manifestation of SLE. To our knowledge, only eight other cases of linear lupus erythematosus profundus have been reported in the literature, five in children. In contrast to our patient, none of those cases progressed to SLE during the reported follow‐up period. The authors report this case to illustrate an unusual superimposed segmental manifestation of an inflammatory polygenic disorder.